Exposure and CBT for chronic back pain: An RCT on differential efficacy and optimal length of treatment - Glombiewski, Julia Anna; Holzapfel, Sebastian; Riecke, Jenny; Vlaeyen, Johan W S; de Jong, Jeroen; Lemmer, Gunnar; Rief, Winfried (Journal of consulting and clinical psychology, 2018)
Our aim was to establish whether Exposure, a specialized tailored treatment for chronic low back pain, has any advantages over cognitive-behavioral therapy (CBT) among individuals with high fear-avoidance levels. Second, we planned to compare short and long versions of Exposure. Third, we aimed to investigate whether Exposure can be delivered in an outpatient psychological setting. A total of 88 Caucasian participants (55% women) were randomized to three different psychological treatment conditions, Exposure-long, Exposure-short, and CBT. All participants were suffering from chronic pain and elevated levels of pain-related anxiety and disability. The primary outcomes were disability (assessed using two different questionnaires, QBPDS and PDI) and average pain intensity; secondary outcomes included pain-related anxiety, psychological flexibility, coping strategies, and depression. Assessments took place at pretreatment, midtreatment, posttreatment, and 6-month follow-up. Exposure was more effective than CBT at reducing movement-related disability assessed with the QBPDS. Exposure and CBT did not differ in reduction of pain intensity or disability assessed using the PDI. Exposure-short outperformed Exposure-long after 10 sessions, meaning that individuals improved faster when they were offered fewer sessions. Exposure could be safely delivered in the psychological setting. Concerning secondary outcomes, Exposure led to greater improvements in psychological flexibility relative to CBT. CBT was more effective than Exposure at enhancing coping strategies. In Exposure, significantly more participants dropped out. Although being more challenging to patients, Exposure is an effective treatment, which can be delivered in a psychological treatment setting and should be offered as a short-term treatment. (PsycINFO Database Record